DATA ANALYSIS IN THE DIGITAL EDUCATION SYSTEM BASED ON A SCIENTIFIC-PEDAGOGICAL APPROACH (Scientific journal of the Fergana State University, 2026)
This article analyzes the scientific and pedagogical nature of data analysis in the digital education system, its importance in managing the teaching process in a person-oriented way, and its role in improving the quality of Education. Within the framework of the article, the theoretical and methodological foundations of the implementation of data analysis in education, the advantages of the approaches to learning analytics and educational data mining, as well  as the prospects for the development of digital analysis mechanisms  in the higher education system of Uzbekistan are covered.